Identification of markers associated with iron and zinc concentration in recombinant inbred lines of brown rice - Kiranmayi, S. L.; Manorama, K.; Venkata, V. G. N. Tripura; Radhika, K.; Cheralu, C.; Roja, V.; Sarla, N. (The Indian Journal of Genetics and Plant Breeding, 2016)
Association of marker and traits were studied using single marker analysis for iron and zinc concentration in rice grains. Grain iron and zinc concentration of rice at two locations was estimated using Atomic Absorption Spectrometer. Across the locations. Iron concentration ranged from 4 to 270 ppm, while that of zinc ranged from 14 to 31 ppm. Parental polymorphism studies identified 82 (11.2%) polymorphic markers from 735 rice microsatellites across 12 chromosomes, and 2 polymorphic markers, ZIPRM 1067 and ZIPRM 5511 out of 36 gene specific primers. The 84 markers with 126 recombinant inbred lines (F6) were used for simple linear regression analysis. A total of 25 markers were significantly associated with iron and/or zinc concentration at one or both locations. Out of these, RM3322 and RM7488 were associated with both iron and zinc.The markers identified may be useful in future breeding programmes aimed at biofortification in rice.